Faktor-faktor Yang Berhubungan Dengan Keaktifan Kader Posyandu Di Wilayah Kerja Puskesmas Baumata Tahun 2021 - Lady Napedi Aome; Muntasir; Sarci M,Toy (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Posyandu is a form of community-based health effort (UKBM) which is managed from, by, and for the community, in order to empower the community and provide convenience to the community in obtaining basic health services. Efforts to improve the function and role of posyandu are not only the responsibility of the government, but also the cooperation of awll components of society, including health workers and cadres. The activity of the cadres will determine whether or not existing posyandu activities will run. Cadre is a community worker who is considered closest to the community itself with its function in mobilizing and empowering the community to create an independent community for healthy living. Based on a report from the Baumata Health Center, the number of posyandu cadres is 170 people who organize various activities at the posyandu. However, in carrying out their duties and functions, not all active cadres carry out their roles well. This study aims to determine what factors are related to the activities of posyandu cadres in the Baumata Health Center Work Area. The type of research used is quantitative research with a cross sectional approach. The sampling used was random sampling and obtained 62 respondents. The analysis used is univariate and bivariate analysis with chi square test. The results showed that the factors related to the activity of posyandu cadres in the working area of ​​the Baumata Health Center in 2021 were family support (p=0.000), awards (p=0.000), knowledge (p=0.000) and training. (p = 0.000).